The Current State of Community Engagement in Urban Soil Pollution Science - Fernández-Viña, Nicole; Chen, Yujuan; Schwarz, Kirsten (Frontiers in Ecology and Evolution, 2022)
Environmental burdens disproportionately impact the health of communities of color and low-income communities. Contemporary and legacy industry and land development may pollute soils with pesticides, petroleum products, and trace metals that can directly and indirectly impact the health of frontline communities. Past efforts to study environmental injustice have often excluded those most impacted, created distrust of researchers and other experts among frontline communities, and resulted in little to no structural change. Prevailing research methods value formal knowledge systems, while often dismissing the knowledge of those most harmed by environmental hazards. Community science has emerged as a process of doing science that centers the participation of community members, who may co-develop research questions, inform study methods, collect data, interpret findings, or implement projects. While community science is one of several research methods that can advance community goals, it can also be implemented in ways that are extractive or harm communities. Research on best practices for community science is robust; however, how community science has been used in urban soil research is not well understood. We identified sixteen relevant urban soil studies published between 2008 and 2021 that used community science methods or engaged with community members around soil pollution. We then assessed the selected studies using two community engagement models to better understand community engagement practices in urban soil pollution science. The Spectrum of Community Engagement to Ownership (SCEO) model, which organizes engagement from level 0 (ignore) to 5 (defer to) was used to assess all studies. Studies that explicitly aimed to co-develop research with the community were additionally assessed using the Urban Sustainability Directors Network High Impact Practices (USDN HIPs). The majority of the studies assessed were aligned with levels 1–3 of the SCEO. Studies assessed as levels 4–5 of the SCEO were associated with delegating power to communities, community engages decision-making, creating space for community voices, and remediation efforts. We propose that future urban remediation soil pollution work that engages at higher levels of the SCEO and employs USDN HIPs, will be more effective at addressing crucial environmental health challenges by supporting, equitable, inclusive, and sustainable solutions.